The Role of Neutrophil Lymphocyte Ratio in Predicting Acute Appendicitis in Adult - Giri, Niraj (Nepal Journal of Multidisciplinary Research, 2022)
Introduction: Acute appendicitis is one of the most common causes of acute abdomen with lifetime occurrence of approximately 7% and with perforation of 17-20%. There are various scoring systems and investigations which are used to ruling in the conditions but none of these are 100% accurate. The aim of this study was to observe relationship between neutrophil lymphocyte ratio (NLR) and simple and complicated acute appendicitis. Methods: This is a prospective observational study conducted for a period of 12 months. Clinical, laboratory and USG parameters were used to diagnose acute. HPE findings were taken as final diagnosis and the objective of the study compared. Results: Total of 100 patients were evaluated in this study. The mean age of the patients with acute appendicitis in this study was 30 years .The mean Alvarado score in this study was 7 and the mean NLR was 6.6. In this study, 24% of case who had TLC of more than 10000 per cubic millimeter had complicated appendicitis (p=0.685). 16% of total cases had complicated acute appendicitis with neutrophil percentage between 81%-90%, 20% with NLR >8 had complicated acute appendicitis and 20% with NLR >8 had HPE proven complicated acute appendicitis (p=0.001) Conclusion: Both neutrophil percentage and NLR were statistically significant in differentiating complicated acute appendicitis from simple acute appendicitis than total leucocyte count alone as shown by study.